Learning Spaces, Competence Training in Professional Performance, and Agricultural Development in Cuba - Arzola de la Rosa, Lissete (2018)
In Cuba, the challenge for universities is to dynamize learning spaces in contexts of economic development, with the relationship between universities and territories being the key to their success. In this paper, we intend to socialize the alternatives that should be assumed for the training of facilitators that articulate in local innovation systems and that departs from the foundations of Education for the development of competences in the professional performance. This way, it contributes to the research of the professional profiles of the local actors who intervene in the processes of development of the food program in Cuba through the application of a questionnaire and discussion groups. The sample used was comprised of various local actors who interact directly in agricultural contexts and perform different functions. The information collected and processing of quantitative data with the use of the SSPS statistical package and for the qualitative data with Nudist Vivo, determined not only the competence portfolios in professional performance, but also the ways to include courses that are inserted in undergraduate and graduate education resulting in the creation of knowledge management processes and innovation for the development of a fair, equitable, and inclusive society.